نهاية التاريخ بين تصوري ماركس وفوكوياما - برابح, عمر (جامعة الوادي - University of Eloued, 2021)
ملخص: يهدف هذا المقال إلى إعادة قراءة تصورين هامين لحركة التاريخ ونهايته، التصور الأول لكارل ماركس الفيلسوف المادي الذي كشف عن زيف تصور هيغل في هذه المسألة، وإن كان قد استعان بأداته التي هي الديالكتيك، والتصور الثاني هو تصور فرانسيس فوكوياما المفكر الأمريكي الذي أعلن عن تصوره بعد تسارع الأحداث التاريخية وانتهاء الحرب الباردة إلى انهيار المعسكر الشيوعي بعد سقوط جدار برلين وتفكيك الاتحاد السوفييتي. إن الغرض من إعادة القراءة هو الكشف عن حدود التصورين خاصة بعد صعود التنين الصيني الذي مثل إلى زمن غير بعيد الإيديولوجيا الاشتراكية من جهة، وتراجع فوكوياما عن كثير من آرائه بعد أحداث الحادي عشر من سبتمبر 2001. ينتهي البحث في هذا المقال إلى الإقرار بصدقية التصورين ونسبيتهما، لأن التاريخ لا توقفه تصورات الفلاسفة أو آراء علماء الدين. Abstract: This article aims to reread two important conceptions of the movement and end of history, the first conception of Carl Marx, the material philosopher who revealed the falsity of Hagel's perception on this issue, although he used his dialectic instruments, and the second is the perception of Francis Fukuyama, the American thinker who announced his vision after the acceleration of historical events and the end of the Cold War to the collapse of the communist camp after the fall of the Berlin Wall and the dismantling of the Soviet Union. The purpose of the rereading is to reveal the limits of the two concepts, especially after the rise of the Chinese dragon, which, not long ago, represented socialist ideology on the one hand, and Fukuyama retracted many of his views after 9/11, 2001. The research in this article concludes by acknowledging the sincerity and relativism of the two conceptions, because history is not stopped by philosophers' perceptions or the views of religious scholars.
مقال
Keywords: مثالية ,مادية ,فلسفة ,نهاية, تاريخ; History , idealism , materialism, final , philosophy